Influence of copper-coated graphene films on mechanical and damping properties of bionic laminar CuAlMn matrix composites - Dongxuan Li; Xiaosong Jiang; Hongliang Sun; Zixuan Wu; Liu Yang (Journal of Materials Research and Technology)
Inspired by the structure of nacre, bionic laminar composites composed of 85.6 wt% Cu, 11.9 wt% Al, and 2.5 wt% Mn were prepared using highly flexible Cu-coated graphene films as fillers. The effects of surface modification and graphene films content on the properties were investigated. Results indicated that the loss factor of composites with 0.1 wt% Cu-coated graphene films is improved by approximately 28% and reaches 0.044 compared to uncoated samples. The density and tensile strength are increased by up to 98% and 362 MPa, respectively. This enhancement is attributed to the improved bonding at the graphene films/matrix interface due to the Cu coating, which allows for efficient load transfer. Concurrently, the activation of interlayer sliding in the graphene films dissipates substantial energy. However, an excessive addition of graphene films leads to decreased density and increased internal defects in the composites, resulting in deteriorated properties. This study provides a reference for the preparation of CuAlMn matrix composites with enhanced mechanical and damping properties.